LTE Cell Load Estimation Based on DCI Message Decoding - Chirkov, D. D.; Gaysin, A. K.; Ashaev, I. P. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
For modern mobile communication systems, the task of analyzing the parameters of quality of service and network information load remains one of the most popular. There are several ways getting this information in LTE networks. For example, by evaluation of test signals or estimation special reference signals in LTE frame. In this paper, it is proposed to obtain information about the cell load by decoding service messages of the DCI control information block. The main idea of this method is that the information load of LTE cell is estimated by decoding DCI messages in the LTE physical control channel and establishing the number of unique identifiers. For decoding the LTE signal, was used MATLAB LTE Toolbox and software-defined radio platform USRP 2920. In the work, the UE detection algorithm was tested on the signal generated using MATLAB software, and evaluated the information load of the network of a real LTE base station.